Protein Expression of Soybean (Glycine Max L. Merr) Varieties In Drought Stress - Savitri, Evika Sandi; Arumingtyas, Estri Laras (El-Hayah : Jurnal Biologi, 2017)
Drought is one of the most severe limitations on the productivity of soybean. There are many genes and proteins involved in drought stress tolerance.Â  Identification of proteins which could be used as the base for the development of molecular study is very important to understand drought tolerance thoroughly. The objective of the research was to investigate protein expression of soybean to drought stress. Changes in protein expression were analyzed using SDS PAGE and two dimensional gel electrophoresis. Image analysis of 2D protein was performed by using the PDQuest 8.0 software program (Bio-Rad). Tolerant variety, Dering-1, was subjected to drought stress using limitation of watering, while Detam-1, a sensitive variety, was used as comparator.Â  The result showed that protein concentration have decreased in drought condition from 3,22 mg/ml to 0,77 mg/ml. The new protein band with the 24,95 kDa have been found in drought condition. This protein is osmotin like protein with the accession number NP915414 which may play a role in the mechanism of drought resistance. The identification of the protein based on sequence amino acid literature review